EDUKASI PENGOBATAN BATUK SECARA MANDIRI “SWAMEDIKASI” DI KAMPUNG HERBAL NGINDEN SURABAYA - Dewi Perwito Sari; IAK Pramushinta; Ira Purbosari (Kanigara, 2022)
Coughing is a reflex that is stimulated by irritation of the lungs or respiratory tract. Cough is usually a symptom of an upper respiratory infection (eg colds, flu) where nasal secretions and phlegm stimulate the respiratory tract. Coughing is also a way to keep the airway clear. Self-medication is a community effort to treat itself. Self-medication is usually carried out to treat complaints and minor ailments that many people experience, such as fever, pain, dizziness, cough, influenza, stomach ulcers, worms, diarrhea, skin diseases and others. Self-medication is an alternative that is taken by the community to increase the affordability of treatment. With this program, it is hoped that the community will be able to have more information regarding cough medicine education independently.